Eye Control Deficits Coupled to Hand Control Deficits: Eye–Hand Incoordination in Chronic Cerebral Injury - Rizzo, John-Ross; Fung, James K.; Hosseini, Maryam; Shafieesabet, Azadeh; Ahdoot, Edmond; Pasculli, Rosa M.; Rucker, Janet C.; Raghavan, Preeti; Landy, Michael S.; Hudson, Todd E. (Frontiers in Neurology, 2017)
It is widely accepted that cerebral pathology can impair ocular motor and manual motor control. This is true in indolent and chronic processes such as neurodegeneration and in acute processes such as stroke or those secondary to neurotrauma. More recently, it has been suggested that disruptions in these control systems are useful markers for prognostication and longitudinal monitoring. The utility of examining the relationship or the coupling between these systems has yet to be determined. We measured eye and hand movement control in chronic, middle cerebral artery (MCA) stroke, relative to healthy controls, in a saccade-to-reach paradigm to assess eye-hand coordination. Primary saccades were initiated significantly earlier by stroke participants relative to control participants. However, despite these extremely early initial saccades to the target, reaches were nevertheless initiated at approximately the same time as those of control participants. Control participants minimized the time period between primary saccade onset and reach initiation, demonstrating temporal coupling between eye and hand. In about 90% of all trials, control participants produced no secondary, or corrective, saccades, instead maintaining fixation in the terminal position of the primary saccade until the end of the reach. In contrast, participants with stroke increased the time period between primary saccade onset and reach initiation. During this temporal decoupling, multiple saccades were produced in about 50% of the trials with stroke participants making between one and five additional saccades. Reaches made by participants with stroke were both longer in duration and less accurate. In addition to these increases in spatial reach errors, there were significant increases in saccade endpoint errors. Overall, the magnitude of the endpoint errors for reaches and saccades were correlated across participants. These findings suggest that in individuals with otherwise intact visual function, the spatial and temporal relationships between the eye and hand are disrupted post-stroke, and may need to be specifically targeted during neurorehabilitation. Eye-hand coupling may be a useful biomarker in individuals with cerebral pathology in the setting of neurovascular, neurotraumatic and neurodegenerative pathology.